REPRESENTASI PELANGGARAN HAK ASASI MANUSIA DALAM FILM “DE OOST/THE EAST” (Analisis Semiotik Charles Sanders Peirce) - Rabani, Olgheri Paco Syah; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica; Damasemil, Calvin (E-Jurnal Medium, 2023)
As one of the mass communication media, film acts as a medium for delivering messages to audiences through audio and visual. “De Oost/The East” is a film that depicts violence during the Indonesian war of independence. This study aims to see the representation of human rights violations in the film "De Oost/The East". The researcher uses a qualitative approach and examines data with the concept of human rights issues and human rights violations, Hall's Representation Theory and Peirce's Triangle of Meaning Theory. The results showed that the film "De Oost/The East" represented gross human rights violations in the form of: (1) Torture, (2) Murder, (3) Extermination. Various forms of human rights violations in the film in accordance with the Rome Statute of the International Criminal Court Article 7 is a form of gross human rights violations, namely crimes against humanity. Keywords : Human Rights Violations, Film, De Oost/The East, Charles S. Peirce.